Proceedings of the Ninth ACM Conference on Hypertext and Hypermedia : Links, Objects, Time and Space---Structure in Hypermedia 1998
DOI: 10.1145/276627.276649
|View full text |Cite
|
Sign up to set email alerts
|

An agenda for open hypermedia research

Abstract: INTRODUCTIONThe historical development of hypermedia systems can be characterized as a series of successive abstractions of functionality away from the "core" hypermedia server, often resulting in a new open layer in the hypermedia environment architecture. Recently, this trend of abstraction has been applied to the hypermedia server itself, replacing the notion of a single, closed hypermedia server with an open layer of structure servers. This newest development brings with it a new set of challenges and rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…Work on the design of an open hypermedia protocol has also been undertaken (Reich et al, 1999). A number of research areas for open hypermedia have been identified (Nürnberg et al, 1998) addressing the human perception and use of hypermedia, hypermedia client-servers, structure servers and hypermedia systems backend. An approach for offering OHS to the WWW has also been proposed by Karousos et al (2003).…”
Section: Ohs Architecturesmentioning
confidence: 99%
“…Work on the design of an open hypermedia protocol has also been undertaken (Reich et al, 1999). A number of research areas for open hypermedia have been identified (Nürnberg et al, 1998) addressing the human perception and use of hypermedia, hypermedia client-servers, structure servers and hypermedia systems backend. An approach for offering OHS to the WWW has also been proposed by Karousos et al (2003).…”
Section: Ohs Architecturesmentioning
confidence: 99%
“…Solutions like the Server Information Management (SIM), which collects server name and location information from servers and distributes it to clients [9], as well as the notion of Hypermedia Resource Descriptors (HRD) that can describe both documents and servers [10], have been proposed. Furthermore, the Open Hypermedia Protocol (OHP), which was initially designed to Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Semantics Into Hypermedia 21 Self-descriptive Hypermedia Sementioning
confidence: 99%
“…Correspondingly we modified the Babylon Web service so as to conform to its description. It is in our imminent plans to investigate the various Component-Based Open Hypermedia Systems [9], as well as the various systems developed under the discipline of Structural Computing [14], like Themis [15], in order to implement corresponding instances, and identify possible required enhancements for the ontology.…”
Section: An Ontology For Hypermedia Servicesmentioning
confidence: 99%
“…So some might specialize in writing scalable high performance servers; others might specialize in implementing feature-packed clients. Also, integrations or adaptations would only have to be done once (9). Furthermore, the increased availability of standard tools would result in a proven and stable platform on which developers could prototype and evaluate their new tools.…”
Section: History and Motivationsmentioning
confidence: 99%